2012
DOI: 10.1209/0295-5075/100/47003
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and metallic conductivity in Tl 0.4 K 0.4 Fe 2−y Se 2−x S x

Abstract: We study the effects of S-doping on the microstructure, magnetic and transport properties of the Tl0.4K0.4Fe2−ySe2−xSx superconductor. At low doping level (x ⩽ 0.8), the samples exhibit behaviors similar to those of the parent sample, i.e., the occurrence of phase separation into a Fe-vacancy phase, a charge ordering phase and an undistorted phase; the presence of a “hump”-like feature in the resistivity curves; and the development of antiferromagnetic order well above room temperature. In sharp contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Figure 3b also shows the appearance of broad bands at about 3400-3200 and 1644 cm −1 in the nanocomposites belonging to hydroxyl and carbonyl amide groups, respectively, due to strong interactions between oxygen groups of rGO and functional groups of the biofilm. [33] The ratio between the carbonyl amide and reference bands was around 0.30 in PrG (0.1), but decreased to 0.17 in PrG (3), as a consequence of a small biofilm formation.…”
Section: Resultsmentioning
confidence: 93%
“…Figure 3b also shows the appearance of broad bands at about 3400-3200 and 1644 cm −1 in the nanocomposites belonging to hydroxyl and carbonyl amide groups, respectively, due to strong interactions between oxygen groups of rGO and functional groups of the biofilm. [33] The ratio between the carbonyl amide and reference bands was around 0.30 in PrG (0.1), but decreased to 0.17 in PrG (3), as a consequence of a small biofilm formation.…”
Section: Resultsmentioning
confidence: 93%
“…This sort of phase separation was not surprising because it is often observed with inorganic materials. For example, in the single crystals of Tl 0.4 K 0.4 Fe 2– y Se 2– x S x , a phase separation into the Tl 0.4 K 0.4 Fe 2– y Se 2– x S x -lattice (the S-poor phase) and the Tl 0.4 K 0.4 Fe 2– y S 2 -lattice (the S-rich phase) at nanoscale has been observed with an increasing concentration of S doping. The powder XRD of Tl 0.4 K 0.4 Fe 2– y Se 2– x S x was completely refined with two sets of lattice constants: (1) a = 3.754 Å and c = 13.651 Å in the S-poor phase, and (2) a = 3.801 Å and c = 13.231 Å in the S-rich phase with the same space group (I4/ mmm) .…”
Section: Resultsmentioning
confidence: 99%
“…This result could be due to the interference of the C O contraction vibration of GO assembled on the CNFs. [29] Additionally, two peaks at 1720 and 1385 cm −1 appeared in the spectral curve of the CNFs/GO (18) composite film and were ascribed to the C O and C─OH stretching vibrations of GO, respectively. [30,31] These changes indicated that the GO nanosheets were closely adhered to the surface of the CNF film through the medium of Cu 2+ .…”
Section: Reduction Of Go By L-ascorbic Acidmentioning
confidence: 99%